Structural and morphological effect of Ti underlayer on Pt/Co/Pt magnetic ultra-thin film. (24th September 2021) - Turksoy Ocal, M.; Sakar, B.; Oztoprak, I.; Balogh-Michels, Z.; Neels, A.; Ozturk, O.
Abstract: Pt( x Å)/Co(5 Å)/Pt(10 Å) trilayer films with x  = 5, 8, and 10 Å were deposited on naturally oxidized Si ( 111 ) substrate to investigate the Ti underlayer effect on perpendicular magnetic anisotropy. A small amount of Ti underlayer promoted the magnetic anisotropy to perpendicular direction for x  = 8 and 10 Å and also affected the growth mode of the trilayer film. The Pt particles preferably grew in the neighborhood of the Ti cluster, giving rise to a relatively smooth layer with a fcc fiber texture ( 111 ) structure. By contrast, the absence of a Ti underlayer led to a clustered, relatively rough, and randomly oriented nano-crystalline growth. Differences in the growth mode appeared as intensity loss in X-ray photoelectron spectroscopy spectra due to shadowing effects. Our results indicate that traceable amount of underlayer can change the magnetic anisotropy of the film by influencing the film growth.